SPEECH FUNCTIONS ANALYSIS USED BY THE MAIN CHARACTER IN “OVER THE MOON” MOVIE (2020) - Dwiningtyas, Ni Made Rima Agustina; Krisnawati, Ni Luh Putu; Malini, Ni Luh Nyoman Seri (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2023)
Speech functions is a study of a variety of utterances used and their function in speech. Utterances are produced during conversations in daily life, including the function of speech. This study aims to analyze whether the speech function occurs in the movie entitled “Over the Moon”, which talks about the adventure of a girl named Fei Fei. The data was taken from the movie and its script. The data were analyzed by using the qualitative descriptive method, through observation and note-taking as methods and techniques to collect the data. The theory used in this study is proposed by Holmes (2013). There are six categories of speech functions namely: expressive, directive, referential, metalinguistic, poetic, and phatic functions. The result shows that out of the six categories, there are five categories of speech functions found in the movie: expressive, directive, referential, poetic, and phatic. Among the five functions, the directive is the most used speech function in the conversation of the movie. The function of speech can differ, depending on the data source used. Each data source has a different plot, theme, style, setting, and situation when the dialogues occur.